Predicting rating changes for banks: How accurate are accounting and stock market indicators? - Isabelle Distinguin; Iftekhar Hasan; Amine Tarazi (Bank of Finland, 2012)
We aim to assess how accurately accounting and stock market indicators predict rating changes for Asian banks. We conduct a stepwise process to determine the optimal set of early indicators by tracing upgrades and downgrades from rating agencies, as well as other relevant factors. Our results indicate that both accounting and market indicators are useful leading indicators but are more effective in predicting upgrades than downgrades, especially for large banks. Moreover, early indicators are only significant in predicting rating changes for banks that are more focused on traditional banking activities such as deposit and loan activities. Finally, a higher reliance of banks on subordinated debt is associated with better accuracy of early indicators.
URN:NBN:fi:bof-20140807539
Keywords: G21; G28; 330; Bank Failure; Bank Risk; Ratings; Emerging Market